Design and nonlinear modeling of a novel planar compliant parallelogram mechanism with general tensural-compresural beams. (October 2020) - Wu, Ke; Hao, Guangbo
Highlights: We present a novel compliant parallelogram mechanism. We use general tensural-compresural beams. We develop and validate the nonlinear kinetostatic model. We conduct a comprehensive analysis of parameters for four single design objectives. Abstract: The paper proposes a novel type of Compliant Mechanism (CM) called Planar Compliant Parallelogram Mechanism (PCPM) for translational movement by synthesizing 8 compliant beams. Half of the beams are arranged in an inverted way while the other half of them are non-inverted, and both the inverted beams and non-inverted beams are arranged symmetrically. The arrangement empowers the mechanism to have a tensural-compresural characteristic with the robustness against beam buckling regardless of the high-payload direction. Moreover, the new mechanism introduces more design parameters than the traditional parallelogram mechanism, providing a broader design space for performance optimization. A nonlinear and analytical model of the mechanism was derived first depending on the Timoshenko Beam Constraint Model (TBCM) for quick design, followed by nonlinear FEA validation. Constraints and other conditions were determined beforehand to prepare for the comprehensive parameter analysis. Comprehensive analysis of geometric parameters was carried out for four single design objectives based on the aforementioned analytical model. It is shown that two types of optimized design were obtained from the parameter analysis where one design involves distributed compliance. Experimental testing was conducted to validate the primary motion stiffness of the distributed-compliance involved design.